PENGARUH KUALITAS LAYANAN, PROMOSI, HARGA DAN KEPERCAYAAN TERHADAP KEPUTUSAN PEMBELIAN JASA (STUDI KASUS JNT EKSPRESS CABANG MLANDINGAN KABUPATEN SITUBONDO) - Salehuddin, Salehuddin; Hafidzi, Achmad Hasan; Rahayu, Jekti (Growth, 2022)
This study was conducted to determine the effect of service quality, promotion, price and trust on purchasing decisions at JNT Ekspress Mlandingan branch. This study uses multiple linear regression analysis test. The population used by all groups of people with respondent criteria is customers who use the services of JNT Express Mlandingan branch at least 2 times. The number of samples used were 50 people who were taken by purposive sampling technique. The results of the partial test (t test) show that service quality, promotion, and trust have no significant effect on purchasing decisions. However, the price variable partially has a significant influence on purchasing decisions at PT JNT Ekspress Mlandingan branch. Keywords: Quality of service, Promotion, Price, Trust and Purchase decision